Kesejahteraan Psikologis Pelajar Sekolah Berasrama: Analisis Hubungan Interpersonal dan Efikasi Diri - Dewi Utami; Dadan Mardani (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This study aims to analyze the psychological well-being of boarding school students with a focus on interpersonal relationships and self-efficacy. This research employs a quantitative approach with a correlational survey design, involving 111 boarding school students in Indonesia. Data collection instrument is questionnaire to measure students’ psychological well-being referencing to two dimensions of self acceptance and positive relation with other. The analysis results indicate that interpersonal relationships and self-efficacy significantly influence students' psychological well-being. The average score for interpersonal relationships was 3.47, for loneliness and social support was 2.63, and for self-confidence was 3.29. These findings highlight the importance of strengthening social relationships and beliefs in students’ ability to complete a task in order to enhance psychological well-being. Recommendations are provided to develop social support programs and self-efficacy training skills in boarding schools.